ACQUITTAL OF THE DEFENDANTS IN THE CRIMINAL TRIAL BASED ON ARTICLE 16(1)(B) OF THE CRIMINAL PROCEDURE CODE - HIGHLIGHTS - Sandra Sophie-Elise OLĂNESCU; Alexandru Vladimir OLĂNESCU (Challenges of the Knowledge Society)
Civil claims not settled by the criminal court may be brought before civil courts, one of which is the delivery of a settlement of acquittal based on Article 16(1)(b) of the Criminal Procedure Code. It is therefore essential to know how these civil claims can be obtained, i.e., what kind of civil action is to be or may be filed, what are the specific features of the shading of the application and the admissibility aspects of such an application. As is the case in majority practice, actions brought by civil parties in a criminal case, where civil action has remained unresolved by the criminal court, are requests for criminal liability to be held. One should not overlook, however, that such an action for civil liability must comply, inter alia, with the requirements set out in Article 1357 of the Civil Code, i.e., it must be proved that the four essential conditions of liability are met, namely: the existence of unlawful conduct, the taking of injury, the causal link between the unlawful conduct and injury and, ultimately, the guilt of the perpetrator. Throughout this paper, we intend to analyze all these issues in detail, by reference to concrete cases, court rulings which have supported the solutions adopted on these issues, as well as relevant doctrinal views on these matters. At the same time, the work will finally redraw its own conclusions on all the issues addressed.